Indocile Bodies: Bodily Transgressions in Selected Canadian Movies - Sikora, Tomasz (Romanica Silesiana)
The article looks at the representations of corporeality, desire and transgression in selected films by David Cronenberg, Guy Maddin and Bruce LaBruce. The body acquires some kind of independence in these films, and the forces of excess that work in/though it (drives, desires) push the modern subject into various acts of transgression, thus threatening its propriety and stability. At a cultural level, this phenomenological instability of body- and self-boundaries may be linked to the Canadian sense of a “weak” national identity, rephrased by some as a positive case of “queer” nationality. Key words: Body, desire, sexuality, transgression, excess, queer, Canadian cinema.